(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background: Bacteria can't grow without iron (Fe), and the majority of them actively seek out Fe ions via specialized proteins called siderophores. Objective: To quantify the prevalence of yersinobactin irp2, salmonellochilin iroN, and aerobactin iucA siderophore genes in the virulent Iraqi strains of uropathogenic Escherichia coli (UPEC). Methods: Fourteen E. coli strains that were previously isolated and diagnosed from urinary tract infections and biologically active siderophore producers. These strains were analyzed for the presence of three siderophore genes (iucA, iroN, and irp2) using conventional polymerase chain reactions (PCR). Results: The frequencies of such iucA, iroN, and irp2 genes among the UPEC isolates were 3 (21.42%), 10 (71.4%), and 4 (28.6%), respectively. Conclusion: Research suggests that siderophores can successfully reduce the pathogenicity of UPEC bacteria. Moreover, their primary function in infection differs depending on the siderophore type and concentration. Yersinobactin irp2 represented the main siderophore gene, followed by salmochelin iroN and aerobactin iucA. Keywords: Escherichia coli, siderophore, aerobactin iucA, salmochelin iroN, yersinobactin irp2. Citation: Younus HS, Mudallal NHA. Molecular detection of siderophore genes in Escherichia coli among Iraqi strains. Iraqi JMS. 2025; 23(1): 164-170. doi: 10.22578/IJMS.23.1.19